Synthesis of 4‐Oxo‐but‐2‐enals through tBuONO and TEMPO‐Promoted Cascade Reactions of Homoallylic Alcohols1. Issue 11 (20th September 2016) - He, Yan; Tian, Miao‐Miao; Zhang, Xin‐Ying; Fan, Xue‐Sen
Abstract: An efficient and stereoselective synthesis of ( E )‐4‐oxo‐but‐2‐enals through tert ‐butyl nitrite ( t BuONO)‐ and 2, 2, 6, 6‐tetramethylpiperidine‐1‐oxyl (TEMPO)‐promoted cascade reactions of homoallylic alcohols is presented. Mechanistically, the formation of the title compounds involves a cascade process including nitration of the carbon–carbon double bond, oxidation of the secondary alcohol unit, and Nef transformation of the in situ formed allylic nitro scaffold. In this process, t BuONO is an efficient nitration and oxidation reagent while TEMPO is believed to act as a mild oxidant and a novel reagent to promote the Nef reaction that is accomplished under mild and neutral conditions. As a further aspect, the ( E )‐4‐oxo‐but‐2‐enals thus obtained were found to be suitable substrates to condense with hydrazine hydrate to give diversely substituted pyridazines with good efficiency. Abstract : Be sure to send OXO : An efficient and highly stereoselective synthesis of ( E )‐4‐oxo‐but‐2‐enals through the cascade reactions of homoallylic alcohols has been developed. Mechanistically, the formation of the title compounds involves a cascade process including nitration of the carbon—carbon double bond, oxidation of the secondary alcohol unit, and the Nef transformation of the in situ formed allylic nitro scaffold.